(untitled) (Dhaka University Journal of Biological Sciences, 2024)
The purpose of the study was to develop a scale for assessing cognitive distortions in Bangladesh and establishing psychometric properties for Bangladeshi population. The scale was named as Bangladesh Cognitive Distortion Scale (BCDS). Items were constructed through three stages of intensive expert evaluation where 128 respondents participated and both item analysis and factor analysis were undertaken. Finalized BCDS with 39 items was administered to 478 respondents to calculate its psychometric properties. Concurrent validity of BCDS was found 0.828 by calculating correlation between the score of BCDS and clinician’s subjective rating. Predictive validity considering anxiety and depression scale was found 0.756 and 0.841, respectively. Convergent validity (0.670) was confirmed through the correlation between the DAS and BCDS and divergent validity was established by the discriminate value (F=649.564, α<0.01) of clinical and non-clinical groups. Internal consistency reliability of BCDS (Cronbach Alpha- 0.962 and test-retest- 0.890) was found very high. The cut-off point for measuring cognitive distortion by BCDS was found 56 with sensitivity 87% and specificity 88%. According to the percentile norm, total score 56 to 72, 73 to 91, 92 to 109, 110 and above represents the mild, moderate, severe, and profound levels of cognitive distortions respectively. BCDS not only will help both clinicians and researchers to assess cognitive distortions within a short time but also could be used as a valid and reliable outcome measure in cognitive behavior therapy. Dhaka Univ. J. Biol. Sci. 33(2): 97-109, 2024 (July)